2018
DOI: 10.1371/journal.pone.0205298
|View full text |Cite
|
Sign up to set email alerts
|

Position effect, cryptic complexity, and direct gene disruption as disease mechanisms in de novo apparently balanced translocation cases

Abstract: The majority of apparently balanced translocation (ABT) carriers are phenotypically normal. However, several mechanisms were proposed to underlie phenotypes in affected ABT cases. In the current study, whole-genome mate-pair sequencing (WG-MPS) followed by Sanger sequencing was applied to further characterize de novo ABTs in three affected individuals. WG-MPS precisely mapped all ABT breakpoints and revealed three possible underlying molecular mechanisms. Firstly, in a t(X;1) carrier with hearing loss, a highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…DSBs are most probably repaired by error-prone NHEJ or microhomology-mediated end joining (MMEJ) mechanisms (Jones and Jallepalli, 2012). In most cases, very short or no microhomology in the chromothripsis breakpoint junctions can be found (Stephens et al, 2011; Chiang et al, 2012; Kloosterman et al, 2012; Malhotra et al, 2013; Weckselblatt et al, 2015; Aristidou et al, 2018; Slamova et al, 2018). However, in a few cases of CC, DSBs were found in high-copy repeats (Nazaryan et al, 2014; Nazaryan-Petersen et al, 2016).…”
Section: Causes and Mechanisms Of Chromothripsismentioning
confidence: 99%
“…DSBs are most probably repaired by error-prone NHEJ or microhomology-mediated end joining (MMEJ) mechanisms (Jones and Jallepalli, 2012). In most cases, very short or no microhomology in the chromothripsis breakpoint junctions can be found (Stephens et al, 2011; Chiang et al, 2012; Kloosterman et al, 2012; Malhotra et al, 2013; Weckselblatt et al, 2015; Aristidou et al, 2018; Slamova et al, 2018). However, in a few cases of CC, DSBs were found in high-copy repeats (Nazaryan et al, 2014; Nazaryan-Petersen et al, 2016).…”
Section: Causes and Mechanisms Of Chromothripsismentioning
confidence: 99%
“…Additionally, Nfib ‐knockout mouse models have been reported to have agenesis or dysgenesis of the corpus collosum and a reduction in the number of midline glial cells (Piper et al, 2009; Steele‐Perkins et al, 2005). The first reports suggesting that disruption of NFIB (MIM: 618286) may be associated with human phenotypes involved copy number variants (CNVs) and translocations, most of which impacted additional genes and were in patients with heterogeneous phenotypes, making the effects of isolated NFIB disruption difficult to establish (Aristidou et al, 2018; Gobius et al, 2016; Redin et al, 2017; Sajan et al, 2013). In 2018, Schanze and colleagues published a cohort of 18 individuals with pathogenic NFIB variants, including patients with microdeletions and single nucleotide variants (Schanze et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The question of the contribution of PAX6 neighboring genes in the 11p13 region to the manifestation of congenital aniridia remains open. Additionally, when chromosome rearrangements are complex, spatial genomic disorganization could worsen the severity of systemic complications [ 17 , 18 ]. It was recently shown that chromosomal aberrations might not lead to disbalance due to gain or loss of genetic material but rather to the disruption of topologically associating domains (TADs), when a large structural variant might disrupt a CTCF-binding boundary, leading to changes in regulation of unaffected genes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%